Enhanced spontaneous DNA twisting/bending fluctuations unveiled by fluorescence lifetime distributions promote mismatch recognition by the Rad4 nucleotide excision repair complex. Issue 3 (18th December 2017) - Chakraborty, Sagnik; Steinbach, Peter J; Paul, Debamita; Mu, Hong; Broyde, Suse; Min, Jung-Hyun; Ansari, Anjum
Abstract: Rad4/XPC recognizes diverse DNA lesions including ultraviolet-photolesions and carcinogen-DNA adducts, initiating nucleotide excision repair. Studies have suggested that Rad4/XPC senses lesion-induced helix-destabilization to flip out nucleotides from damaged DNA sites. However, characterizing how DNA deformability and/or distortions impact recognition has been challenging. Here, using fluorescence lifetime measurements empowered by a maximum entropy algorithm, we mapped the conformational heterogeneities of artificially destabilized mismatched DNA substrates of varying Rad4-binding specificities. The conformational distributions, as probed by FRET between a cytosine-analog pair exquisitely sensitive to DNA twisting/bending, reveal a direct connection between intrinsic DNA deformability and Rad4 recognition. High-specificity CCC/CCC mismatch, free in solution, sampled a strikingly broad range of conformations from B-DNA-like to highly distorted conformations that resembled those observed with Rad4 bound; the extent of these distortions increased with bound Rad4 and with temperature. Conversely, the non-specific TAT/TAT mismatch had a homogeneous, B-DNA-like conformation. Molecular dynamics simulations also revealed a wide distribution of conformations for CCC/CCC, complementing experimental findings. We propose that intrinsic deformability promotes Rad4 damage recognition, perhaps by stalling a diffusing protein and/or facilitating 'conformational capture' of pre-distorted damaged sites. Surprisingly, even mismatched DNA specifically bound to Rad4 remains highly dynamic, a feature that may reflect the versatility of Rad4/XPC to recognize many structurally dissimilar lesions.